Rehabilitation of Swallowing Functions by a New Concept of Intralaryngeal Prostheses. (2nd September 2014) - Schultz, Philippe; Dupret‐Bories, Agnès; Vrana, Engin; Riehm, Sophie; Guillere, Florence; Lavalle, Philippe; Debry, Christian
Abstract : Objectives: Describe 2 intralaryngeal prostheses (ILP) designed to treat laryngeal sphincter incompetence. Present the development of these new devices and analyze the improvement of swallowing. Methods: Patients presented with moderate to severe swallowing disorders due to neurological disease or after head and neck cancer treatment were included in this study. All patients required a tracheostomy and a feeding tube to fulfill the inclusion criteria. Two ILP were evaluated: (1) a closed silicone prosthesis (CP), Novatech; (2) a silicon open prosthesis cover with a double flow valves (VP), opened during respiration and closed during swallowing (Newbreez, Protip, France). The devices were inserted under endoscopy. The swallowing functions were assessed from postoperative day 2 and scored using the swallowing performance status scale (SPS). Results: Nineteen patients were included. Eleven patients, presented with neurological disease, received CP. Eight patients suffering from neurological disease (n = 4) or from swallowing disorders after radiotherapy (n = 4) received a VP. CP stopped aspiration in 11 patients, allowing a partial oral feeding in 6 patients and the withdrawal of the prostheses after a partial neurological recovery in 4 patients. VP decreased laryngeal aspiration of food or saliva, allowing to continue partial oral feeding and to speak with a whispered voice. Conclusions: CP prevents laryngeal aspiration, allowing swallowing reeducation during the phase of neurological recovery. VP is still on assessment in order to propose to patients with moderate swallowing disorders to keep laryngeal phonation and respiration.